Os efeitos jurídicos do preenchimento do PPP (Perfil Profissiográfico Previdenciário) no contexto trabalhista e previdenciário - Nicastro, Pedro Henrique Waldrich (Universidade do Vale do Rio dos Sinos, 2025)
This paper analyzes the importance of completing the PPP (Professional Social Security Profile) form in social security legislation for the recognition of special activity in the granting of social security benefits with Social Security and also in the field of labor law. It addresses the legal effects of filling out the PPP form with false information about the reality of the work environment that the insured will have to face, demonstrating the Judiciary's resistance to granting expert evidence. Therefore, the objective of this paper was to propose a legislative proposal with grounds considered sufficient and objective for challenging the PPP form, with the predictability of the acceptance of expert evidence. The first chapter presents the benefits and generalities of the social security legislation that governs the recognition of special activities. It then highlights the importance of conducting a technical expert assessment in social security disputes when there are discrepancies between the information in the PPP form and the reality of the workplace. The chapter also demonstrates the similarities between the recognition of special activities and the recognition of the hazardous work allowance in the labor sphere. Finally, the right to produce expert evidence in social security proceedings is analyzed, which should be treated as a rule, in addition to presenting a legislative proposal as a way to guarantee predictability and legal certainty for those under its jurisdiction.
Keywords: Perfil Profissiográfico Previdenciário (PPP); Aposentadoria especial; Riscos ambientais; Insalubridade; Perícia técnica pericial; Social Security Professional Profile (PPP); Special retirement; Environmental risks; Unhealthiness; Expert technical expertise; ACCNPQ::Ciências Sociais Aplicadas::Direito